2021
DOI: 10.3390/agriculture11121191
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Essential Oil and Trans-Anethole Yield of Fennel (Foeniculum vulgare Mill. var. vulgare) by Application Artificial Neural Network and Multiple Linear Regression Methods

Abstract: Foeniculum vulgare Mill. (commonly known as fennel) is used in the pharmaceutical, cosmetic, and food industries. Fennel widely used as a digestive, carminative, galactagogue and diuretic and in treating gastrointestinal and respiratory disorders. Improving low heritability traits such as essential oil yield (EOY%) and trans-anethole yield (TAY%) of fennel by direct selection does not result in rapid gains of EOY% and TAY%. Identification of high-heritable traits and using efficient modeling methods can be a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…The rate obtained from Foeniculum vulgare samples was 2.31% greater than that obtained from Citrus sinensis sample which was 1.8%, followed by Artemisia herba alba samples 1.22% (Table 1). This rate is low when compared to that obtained from Foeniculum vulgare from Iran and Turkey, which is 3.77 and 2.67% respectively (Sabzi-Nojadeh et al, 2021). In addition, the essential oil yields for Citrus sinensis fresh fruits reported in this study are similar to those reported by Bhandari et al (2021).…”
Section: Essential Oils Yield (%)supporting
confidence: 75%
“…The rate obtained from Foeniculum vulgare samples was 2.31% greater than that obtained from Citrus sinensis sample which was 1.8%, followed by Artemisia herba alba samples 1.22% (Table 1). This rate is low when compared to that obtained from Foeniculum vulgare from Iran and Turkey, which is 3.77 and 2.67% respectively (Sabzi-Nojadeh et al, 2021). In addition, the essential oil yields for Citrus sinensis fresh fruits reported in this study are similar to those reported by Bhandari et al (2021).…”
Section: Essential Oils Yield (%)supporting
confidence: 75%
“…A slightly higher accuracy of the ANN model (R = 0.99) when compared to SVM (R = 0.97) was reported by Afradi and Ebrahimabadi [47] who used AI methods to predict the penetration rate of tunnel boring machine. Sabzi-Nojadeh et al [48] compared the accuracy of ANN and MLR models used to predict the oil yield and trans-anethole yield of fennel populations; ANN performed better (R = 0.96 and R = 0.88) than MLR (R = 0.74 and R = 0.68).…”
Section: Discussionmentioning
confidence: 99%
“…Tese cells do not come together randomly, but rather follow a specifc architecture that consists of three types of neuron layers: input, hidden, and output layers. Te input layer is responsible for taking in information from the outside world and transferring it to the hidden layers [22][23][24]. Some networks do not process any information in the input layer at all.…”
Section: Artifcial Neural Network (Anns)mentioning
confidence: 99%